Palingeniusz, „Zodiak życia”, ks. III: „Bliźnięta” - Drzewiecka, Ewelina (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The paper presents a new Polish translation of the third book of Zodiacus vitae (1536) by Marcello Palingenio Stellato (Palingenius) with a short introduction and commentary.